2015
DOI: 10.3344/kjp.2015.28.2.75
|View full text |Cite
|
Sign up to set email alerts
|

What is the Role of Epidural Injections in the Treatment of Lumbar Discogenic Pain: A Systematic Review of Comparative Analysis with Fusion

Abstract: BackgroundLumbar discogenic pain without pain mediated by a disc herniation, facet joints, or the sacroiliac joints, is common and often results in chronic, persistent pain and disability. After conservative treatment failure, injection therapy, such as an epidural injection, is frequently the next step considered in managing discogenic pain. The objective of this systematic review is to determine the efficacy of lumbar epidural injections in managing discogenic pain without radiculopathy, and compare this app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…They included various types of drug therapies including nonsteroidal anti-inflammatory agents, acetaminophen, and anticonvulsants. However, they have not included multiple interventional techniques which have been shown to be significantly effective based on high quality RCTs and appropriately conducted systematic reviews (82,414,(487)(488)(489)(490)(491)(492)(493)(494)(495)(496)(497)(498)(499)(500)(501)(502)(503)(504)(505)(506). However, there also have been multiple discordant opinions with lack of efficacy (507-510).…”
Section: Effectiveness Of Nonopioid Pharmacological and Nonpharmacolomentioning
confidence: 99%
See 2 more Smart Citations
“…They included various types of drug therapies including nonsteroidal anti-inflammatory agents, acetaminophen, and anticonvulsants. However, they have not included multiple interventional techniques which have been shown to be significantly effective based on high quality RCTs and appropriately conducted systematic reviews (82,414,(487)(488)(489)(490)(491)(492)(493)(494)(495)(496)(497)(498)(499)(500)(501)(502)(503)(504)(505)(506). However, there also have been multiple discordant opinions with lack of efficacy (507-510).…”
Section: Effectiveness Of Nonopioid Pharmacological and Nonpharmacolomentioning
confidence: 99%
“…As a composite analysis of multiple systematic reviews, most interventional techniques have been shown to be with at least moderate evidence. Multiple systematic reviews assessing the effectiveness of epidural injections in managing chronic spinal pain with RCTs (487)(488)(489)(490)(491)(492)(493)(494)(495)(496) have shown significant effectiveness of epidural injections in managing spinal pain. The evidence has been variable with somewhat of a stronger evidence for disc herniation and radiculopathy compared to spinal stenosis.…”
Section: Effectiveness Of Nonopioid Pharmacological and Nonpharmacolomentioning
confidence: 99%
See 1 more Smart Citation
“…Disc herniation has been well described in the literature. However, the pain emanating from pathologic changes within the disc itself, without disc herniation (1,34,35,(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99), was described before the classic description of disc herniation. Mixter and Barr described lumbar discectomy in 1934 (100).…”
Section: Introductionmentioning
confidence: 99%
“…One of the classic interventional or minimally invasive approaches is epidural steroids or the application of small amounts of steroids to specific sites within the epidural space [15]. It is thought to decrease inflammation reduce nociceptive input from neural structures, resulting in improved pain scores, function and decrease opiate consumption in patients with acute radiculopathies secondary to disk herniations.…”
Section: Epidural Steroid Injectionsmentioning
confidence: 99%